THE PHILOSOPHICAL UNDERSTANDING OF COMPASSION AS A METHODOLOGICAL FOUNDATION FOR ITS FORMATION IN PRIMARY SCHOOL CHILDREN - Solovyova, Tatiana; Guseva, Victoria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The relevance of the article is determined by the need for a philosophical aspect in the study of the category "compassion" for the discovery and understanding of new pedagogical possibilities of educational activity in primary school. The purpose of the article is to convey to the pedagogical community the quintessence of the philosophical positions reflecting the ideas of compassion in world culture.The methodology of the present study was the civilizational and axiological approaches; the historical and genetic method (theoretical), the study of the experience of educational organizations and personal pedagogical experience in school (empirical) were used in the work.The authors concluded that compassion in the process of education should be perceived as a priority of moral health of the pupils. The compassion is "stored" in the "collective unconscious" of humanity, reflecting the thoughts and feelings common to all people, resulting from their common emotional past. For formation at pupils of compassion it is essential to cause them emotional response created by the teacher, the pedagogical situation, that there is some "moral habit" ("emotional skill"), a member of the "Super-Ego" personality, in other words, conscience. The authors show the ways and methodical means that provide awakening, raising from the depths of the subconscious some innate need to do goodness, the desire to help.